Correlation of preoperative imaging characteristics with donor outcomes and operative difficulty in laparoscopic donor nephrectomy. Issue 3 (23rd October 2019) - Schwartz, Fides R.; Shaw, Brian I.; Lerebours, Reginald; Vernuccio, Federica; Rigiroli, Francesca; Gonzalez, Fernando; Luo, Sheng; Rege, Aparna S.; Vikraman, Deepak; Hurwitz‐Koweek, Lynne; Marin, Daniele; Ravindra, Kadiyala
Abstract : This study aimed to understand the relationship of preoperative measurements and risk factors on operative time and outcomes of laparoscopic donor nephrectomy. Two hundred forty‐two kidney donors between 2010 and 2017 were identified. Patients' demographic, anthropomorphic, and operative characteristics were abstracted from the electronic medical record. Glomerular filtration rates (GFR) were documented before surgery, within 24 hours, 6, 12, and 24 months after surgery. Standard radiological measures and kidney volumes, and subcutaneous and perinephric fat thicknesses were assessed by three radiologists. Data were analyzed using standard statistical measures. There was significant correlation between cranio‐caudal and latero‐lateral diameters ( P  < .0001) and kidney volume. The left kidney was transplanted in 92.6% of cases and the larger kidney in 69.2%. Kidney choice (smaller vs. larger) had no statistically significant impact on the rate of change of donor kidney function over time adjusting for age, sex and race ( P  = .61). Perinephric fat thickness (+4.08 minutes) and surgery after 2011 were significantly correlated with operative time ( P  ≤ .01). In conclusion, cranio‐caudal diameters can be used as a surrogate measure for volume in the majority of donors. Size may not be a decisive factor for long‐term donor kidney function. Perinephric fat around the donor kidney should be reported to facilitate operative planning. Abstract : Imaging characteristics obtained from preoperative CT scans can help anticipate operative difficulty and donor outcomes for optimal management.